P611 A real-world assessment of golimumab effect on quality of life, healthcare resource utilisation and work productivity in patients with ulcerative colitis in Greece: interim results from the GO-LIFE study. (25th January 2019) - Mantzaris, G; Gatopoulou, A; Christodoulou, D; Katsanos, K; Mouzas, I; Tzouvala, M; Paspatis, G; Thomopoulos, K; Michopoulos, S; Koujlakis, G; Pachiadakis, I; Triantafyllou, K; et al.
Abstract: Background: GO-LIFE is an observational, prospective study assessing the impact of golimumab (GLM) on health-related quality of life (HRQoL) and other patient-reported outcomes in patients with ulcerative colitis (UC) in real-world clinical practice. This interim analysis presents the 6-month results. Methods: Eligible patients had moderate-to-severe UC (total Mayo score 6–12, endoscopy subscore ≥2), inadequate response to conventional therapy and were anti-TNFa naïve. GLM was administered per label (no dose optimisation applied). Primary objective was the assessment of the clinically meaningful HRQoL improvement rate, defined as ≥16-point increase in Inflammatory Bowel Disease Questionnaire (IBDQ-32) score from baseline (BL) to 6 months. Other endpoints included assessments of the impact of GLM on: treatment satisfaction, with the Treatment Satisfaction Questionnaire for Medication (TSQM-14); UC-related healthcare resource utilisation (HCRU) during the 6-month period prior to BL vs. 6-month follow-up period; work productivity with the Work Productivity and Activity Impairment (WPAI:UC) questionnaire; and disease activity with the total/partial Mayo score (for patients without endoscopy at 6 months, only the partial Mayo score was used). Results: Fifty patients with mean ± SD UC duration of 8.1 ± 8.1 years were included in the interim analysis; 37 (74%) patients completed the 6-month follow-up. Clinically meaningful HRQoL improvement from BL to 6 months was achieved by 27/50 patients (54%; 95% CI: 39%–68%). All TSQM-14 dimensions improved at 6 months vs. BL; mean ± SD change was significant for effectiveness: 18.0 ± 28.9 ( p < 0.001) and convenience: 10.2 ± 21.8 ( p = 0.002), and nonsignificant for side effects and global satisfaction:6.8 ± 24.9 ( p = 0.142) and 6.2 ± 30.7 ( p = 0.182), respectively. HCRU was reduced during the follow-up period vs. the 6-month period prior to BL (table). All WPAI:UC domain scores improved at 6 months vs. BL; improvement was significant for absenteeism ( p = 0.039), work productivity loss ( p = 0.025) and activity impairment ( p = 0.044). For 28 patients, total Mayo score was not available (no endoscopy done) at 6 months (13 patients did not reach the 6 month visit and for 15 patients endoscopy was not available at 6 months). Clinical response was achieved by 32 (64%) patients and clinical remission by 27 (54%) patients, using the partial Mayo score. Conclusions: In real-world practice GLM improved HRQoL, treatment satisfaction, HCRU, work productivity and disease activity in patients with moderate to severe UC. The study was funded by Merck Sharp and Dohme S.A., Greece.